Gerakan Literasi Keuangan Syariah Mengedukasi Masyarakat Dalam Memahami Produk Keuangan - Anita Anita; Muhammad Irfan Pratama; Harold Kevin Alfredo (CV. Ulil Albab Corp, 2024)
The Shari'ah financial literacy movement is a strategic effort to support the government in educating the public to understand Islamic financial products. Islamic financial products have three pillars, among others, Promoting education programs and national financial literacy campaigns, Strengthening financial literacy infrastructure. With the rapid sharia industry sector and the sizeable Muslim population in Indonesia, it has an impact on the importance of Islamic Financial Literacy to introduce Islamic financial products to the public. This study uses the Library Review method by exploring various reports and journals that are available to obtain information regarding the background of the problem. The purpose of this study was to determine the effectiveness of the Islamic financial literacy movement that has been carried out by the Financial Services Authority (OJK) and other Financial Institutions to find the right solution for the acceleration of Islamic Financial Literacy.